Development of graphene oxide in mixed matrix and thin film composite membranes for removal of acetaminophen from water - Ntone, Ellora Priscille Ndia (2024)
The increasing occurrence of pharmaceutical contaminants in water sources poses a significant environmental and health challenge. This study explores the development of advanced membrane materials for the efficient removal of acetaminophen (ACT) fromwater, which is a commonly used pharmaceutical. Graphene oxide (GO), with its unique physicochemical properties, is employed to enhance membrane performance. A range of 0-0.5 wt% of GO was used for this study. Two distinct membrane configurations are investigated: mixed matrix membranes (MMM) and thin-film composite (TFC) membranes. In MMM, GO is incorporated into a polymer matrix to form a hybrid membrane, while in TFC, a selective GO layer was deposited onto a porous support substrate. Both configurations were designed to maximize ACT removal efficiency while maintaining high water permeability. The results demonstrate that GO incorporation significantly enhanced ACT removal while maintaining acceptable water flux. Membrane containing 0.4 wt% GO was the best performing membrane for the MMMs with permeability of 11.61 L/m2·h·bar and the lowest performance was the membrane with 0.1 wt.% GO with 2.53 L/m2·h·bar. Similarly, best the rejection efficiency was observed at membrane containing 0.4 wt% with at 98.53% at 10ppm of ACT, 97.44% at 20 ppm of ACT and 94.86% at 50 ppm of ACT and the lowest rejection efficiency was observed at membrane containing 0.1 wt% GO with 78.96% at 10 ppm of ACT, 72.72% at 20 ppm of ACT and 68.9% at 50 ppm of ACT. On the other hand, the best performing membrane for TFCs was the membrane with 0.2 wt% GO with permeability of 7.35 L/m2·h·bar while the lowest was the membrane with no GO contain with permeability of 4.33 L/m2·h·bar. Similarly the membrane with 0.2 wt% GO had the best performance in ACT rejection efficiency with 97.7% at 10 ppm of ACT, 95.34% at 20 ppm of ACT and 91.56% at 50 ppm of ACT. The lowest rejection performance was observed at membrane containing 0.4 wt% GO with 73.56% at 10ppm of ACT, 72.07% at 20 ppm of ACT and 67.44% at 50 ppm of ACT. The results demonstrated that GO incorporation significantly enhanced ACT removal while maintaining acceptable water permeability. However, excess concentration of GO on the surface of the membrane causes saturation and agglomeration on the surface of the membrane hence reducing its performance. Additionally, the adsorption equilibrium study was performed on the MMMs to confirm their kinetic and isotherm adsorption properties. The developed MMM and TFC membranes exhibit promising performance, suggesting their applicability in water treatment processes. This research contributes to the ongoing efforts to develop sustainable and efficient membrane technologies for the removal of emerging contaminants from water sources.